Bibliometrik dalam Penelitian Budaya Buton: Mengungkap Pola dan Tren - Malim, Dinna Dayana La Ode; Agustine, Restiyana; Manaf, Abdul (Balitbangda Kota Baubau, 2024)
Indonesia is rich in cultural diversity that is the identity of the nation, and one important part of this diversity is Buton, a former sultanate that joined the Republic of Indonesia in 1961. The ex-sultanate of Buton has a very rich civilization and culture. Since post-1990, research and publications on Buton have grown rapidly, with various themes discussed by cultural figures and academics, both locally and internationally. However, most of this research has not been comprehensively mapped through bibliometric analysis. Therefore, the purpose of this study is to analyze the patterns and trends of Buton cultural research using a bibliometric analysis approach. This study uses the Systematic Literature Review (SLR) method which refers to systematic literature studies, with documents collected through Google Scholar using Publish or Perish. Document screening using the PRISMA method resulted in 261 articles that met the specified criteria, and data analysis was carried out using R Studio with the Bibliometrix-Biblioshiny package. The results of the study show a significant increase in research on Butonese culture, with the trend starting in 2007 and continuing to grow until it peaked in 2023. This trend reflects the growing interest in Butonese local culture, both among academics and the public, making it an important focus in cultural studies in Indonesia. This phenomenon also shows the existence of a relatively focused research community in Butonese cultural studies, with topics that focus on cultural values, language, heritage, and preservation efforts, which are closely related to the history and traditions of the Butonese people. Based on these findings, it is recommended to increase and expand collaboration between academics, cultural figures, and stakeholders to deepen studies on Butonese culture.